Integrated biosensors for monitoring microphysiological systems (vol 22, pg 3801, 2022) - Mou, Lei; Mandal, Kalpana; Mecwan, Marvin Magan; Hernandez, Ana Lopez; Maity, Surjendu; Sharma, Saurabh; Herculano, Rondinelli Donizetti [UNESP]; Kawakita, Satoru; Jucaud, Vadim; Dokmeci, Mehmet Remzi; Khademhosseini, Ali (Royal Soc Chemistry, 2024)
Correction for 'Integrated biosensors for monitoring microphysiological systems' by Lei Mou et al., Lab Chip, 2022, 22, 3801-3816, https://doi.org/10.1039/D2LC00262K.